Development of a mechanistic model for geosynthetic-reinforced flexible pavements. Issue 6 (November 2005) - Kwon, J.; Tutumluer, E.; Kim, M.
Abstract : Geogrids and geotextiles enhance the performance and design of flexible pavements by providing geosynthetic reinforcement to the pavement structure. The structural performance of a layered pavement system is improved through the use of geogrids and high-strength geotextiles as base and sub-base reinforcement. Based on the finite element methodology, a non-linear mechanistic model was developed and utilized to investigate the structural benefit provided by geosynthetic reinforcement. The non-linear mechanistic model was employed to compare responses predicted from isotropic and cross-anisotropic characterizations of the granular base layer in unreinforced and geosynthetic-reinforced conventional flexible pavements. Results indicated that the use of a high-stiffness geogrid reinforcement typically reduced critical pavement responses, computed due to traffic loading and used primarily in mechanistic-based pavement thickness design. Higher percentage reductions in critical pavement responses, and thus increased geogrid reinforcement benefits, were often realized from the cross-anisotropic base characterization. Another indicator of this benefit was the computed stiffening of the granular base and subgrade layers, which could be demonstrated by the small modulus increases in the vicinity of the geogrid reinforcement.